Shift of the photoelectron momentum against the radiation pressure force in linearly polarized intense midinfrared laser fields - Kahvedzic, Resad; Gräfe, Stefanie (Physical Review A, 2022)
The propagation direction momentum component of direct photoelectrons emitted by ionization of an atomic target in an intense, linearly polarized, midinfrared laser field is analyzed. Within the dipole approximation, the average value of this component is zero. However, when nondipole corrections are included, it becomes nonzero. Applying the saddle-point approximation to compute the integral over the ionization times in the expression for the nondipole strong-field approximation differential ionization rate, we surprisingly find a negative momentum shift, corresponding to a shift against the radiation pressure force. Our analysis shows that there is a positive contribution originating from individual ionization pathways within one optical cycle. The interference of contributions from ionization pathways arising within the same optical cycle of the field (intracycle interference) causes an oscillatory behavior, which, crossing to negative values, induces the shift against the radiation pressure force.
CRIS-Team Scopus Importer:2023-04-20